Moderating role of capital market openness between ESG and firm value among public listed companies in China - Hao, Yanrou; Chin, Sok Fun; Nik Abdullah, Nik Herda (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
ESG is the abbreviation of Environmental, Social, and Governance. It pursues the co-development of economic and social values and reflects sustainable development issues at the micro level of enterprises. Based on the exogenous policies by China’s government to promote capital market openness via the two platforms, “Shanghai-Hong Kong Stock Connect” and “Shenzhen-Hong Kong Stock Connect” (Stock Connect), this study selected the data of 6818 firm-years of China public listed companies (2009-2022) as samples and used fixed effects models to investigate how ESG affected firm value and how capital market openness moderated this relationship. The results showed that ESG performance enhanced firm value, and capital market openness policy positively moderated the relationship. The study contributes to the Sustainable Development Theory, Signaling Theory, Agency Theory and Stakeholder Theory to explain the moderating role of capital market openness. From a policy perspective, implementing capital market openness plays an important role in promoting ESG practices to enhance economic growth and globalization amongst China’s public listed companies. Practically, investors and firms should take advantage of capital market openness policies to integrate ESG into their decision-making processes to achieve stable and sustainable long-term value.